Pengaruh Suhu dan Waktu Maserasi terhadap Aktivitas Antioksidan Ekstrak Buah Asam Gelugur (Garcinia atroviridis Griff. ex T.Anderson) - Nicholas Wilbert; I Dewa Gde Mayun Permana; Luh Putu Trisna Darmayanti (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Asam gelugur fruit (Garcinia atroviridis Griff. ex T.Anderson) is a local commodity rich in bioactive compounds with potential as a natural antioxidant source, but its utilization remains suboptimal. Extraction of bioactive constituents from asam gelugur fruit allows its utilization as a natural source of antioxidants. This study aims to determine the effect of temperature and maceration time on antioxidant activity and to determine the optimal combination of temperature and maceration time to produce extracts with the highest antioxidant activity. A completely randomized factorial design (CRFD) was used, with two factors: maceration temperature (30, 45, 60°C) and maceration time (12, 24, 36 hours). All data were analyzed using two-way analysis of variance and Tukey’s Honestly Significant Difference (HSD) test. The results showed that the interaction of temperature and time had a highly significant (P≤0,01) effect on total phenolics content, total flavonoid content, and antioxidant activity (IC₅₀), and a significant effect (P≤0,05) on vitamin C content. The best treatment to obtain asam gelugur fruit extract with the highest antioxidant activity was maceration at 30°C for 36 hours, with total phenolics of 10.49±0.12 mg GAE/g, total flavonoids of 3.16±0.28 mg QE/g, vitamin C content of 18.92±0.54 mg AAE/g, and IC₅₀ value of 1.08±0.02 mg/mL.